Management and university organization to face the COVID-19 pandemic. Contributions from the public university in Colombia - Bedoya-Dorado, Cristian (2022)
This article analyses the university management developed in a public institution in the initial stage and during the pandemic in Colombia in 2020. The case study method was used to identify the strategies implemented by the institution to face the crisis from the planning, academic management, administrative management, welfare management, research management, and extension. The results show a configuration of university management that was mainly oriented to guarantee the processes of teaching and face-to-face attendance assisted by technology, to support students economically and psychologically through strategies of articulation with other entities, and to withstand the national crisis through academic research and knowledge.